Effects of indoor air quality on the occupant's health and productivity in an office building - Pratama Putra, Jouvan Chandra (2015)
Indoor Air Quality (IAQ) is an important parameter in deciding the status of Sick Bulding Syndrome (SBS). Poor IAQ which leads to SBS can result in adverse effect on the health of the occupant which causing lower productivity. This study was conducted to establish correlation between IAQ and employee’s productivity. Five parameters of IAQ which include air velocity, air temperature, relative humidity, particulate matters ≥ 0.3 μm and CO2 were considered in this study. The values of these parameters were measured using Davis Anemometer, Particle Counter GT 521 and YES Plus LGA Meter. The measured data were then used as an input data for simulation model of the room using Comsol Multiphysics software. The simulation generated the indoor air velocity of the room and particle distribution. For validation purpose, only the predicted velocity was compared with the measured value, and found that the percentage difference were in the range of 1.5% to 8.45% (below than 10%). Once the model had been validated, the parametric study of air supply inlet position was conducted on the model and found that the position of air supply inlet with x = 2.5 ft, y = 10 ft and H = 6.5 ft give the most efficient air distribution model for diluting the impurities due to the particulate. The questionnaire survey distributed amongst the occupants of the room showed that the occupants were less satisfied (75%) with the IAQ which can lead to SBS problem. The analysis of correlation between IAQ and occupant's productivity depicted that both of the factors were correlated with Rank-Spearman value of 0.648. This study serves as a good platform in assessing IAQ based on the modelling and simulation approach.